2013
DOI: 10.1002/jwmg.606
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior of white‐tailed deer at concentrated food sites as affected by population density

Abstract: Concentrated food sources are used frequently in white-tailed deer (Odocoileus virginianus) management and research, but because such food sources are easily defended, aggressive interactions among deer may influence their effectiveness. The objectives of this study were to determine if deer population density or season affect 1) the order or degree of social dominance among different age and sex groups of white-tailed deer, 2) the rate at which aggressive interactions occur, 3) the severity of interactions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…We assigned each deer to a sex‐age class of juvenile, yearling male, adult female, or adult male based on pelage (for fawns) and morphological characteristics (rostrum length, body size, and antler presence; Donohue et al. ). We assigned group size to each observation by tallying the number of deer in the image.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We assigned each deer to a sex‐age class of juvenile, yearling male, adult female, or adult male based on pelage (for fawns) and morphological characteristics (rostrum length, body size, and antler presence; Donohue et al. ). We assigned group size to each observation by tallying the number of deer in the image.…”
Section: Methodsmentioning
confidence: 99%
“…For juveniles, we included the presence of any male because both adult and yearling males are dominant over juveniles and thus may reduce feeding (Donohue et al. ). We scaled and centered all continuous predictors to facilitate parameter estimation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such aggregation has consequences for social behavior, as well as inter-and intra-specific interactions and stress levels. Aggression (Donohue et al 2013) and stress (Forristal et al 2012) both increase with ungulate density, and 4/5 studies observed higher levels of aggression associated with feeding (e.g., Pérez-González et al 2010).…”
Section: Evidence Of Unintended Effects Of Feedingmentioning
confidence: 99%